(untitled) (Fiep Bulletin - online, 2016)
Aimed to identify the levels of overweight and obesity in children and adolescents in the municipal schools of Arapiraca-AL. The transversal study had a sample of 1378 students of both genders enrolled in 2010. figures concerning the total body mass and height (to calculate Body Mass Index - BMI) were collected. We used the statistical central tendency. For both genders, the results pointed to a profile within the normal range for both BMI. However, when analyzed by gender, levels of overweight and obesity were 21.64% for females and 16.98% for males. We conclude that students of both sexes showed normal levels of BMI, however by gender, girls reported higher levels of overweight corroborating with the current literature.